Nefopam, a non-opioid analgesic, does not alleviate experimental work/effort dyspnoea in healthy humans: A randomised controlled trial. (August 2016) - Dangers, Laurence; Laviolette, Louis; Charbit, Bény; Similowski, Thomas; Morélot-Panzini, Capucine
Abstract: Background: Dyspnoea is a distressing and debilitating symptom with a major impact on quality of life. Alleviation of dyspnoea therefore constitutes a major clinical challenge. When causative physiological disorders cannot be corrected ("persistent dyspnoea"), nonspecific treatment must be considered. Morphine alleviates dyspnoea but has numerous side-effects including ventilatory depression, which justifies looking for alternatives. Certain forms of dyspnoea involve C-fibres, and can be attenuated by C-fibres blockade. We hypothesised that nefopam, a non-sedative benzoxazocine analgesic known to block the transient receptor potential vanilloid subtype 1 abundantly present on C-fibres, would attenuate dyspnoea. Methods: We conducted a randomised, double-blind, placebo-controlled crossover study of nefopam in healthy subjects submitted to experimental work/effort dyspnoea by inspiratory threshold loading (15 healthy male volunteers; age 23–41). We studied a perceptual outcome (dyspnoea visual analogue scale —D-VAS—) and a neurophysiological outcome (effect of nefopam on dyspnoea-pain counter-irritation as assessed by laser-evoked potentials; an effect of nefopam on dyspnoea was hypothetised to reduce the ability of dyspnoea to inhibit pain). Somaesthetic evoked potentials (SEPs) were studied as a control. Results: A statistically significant decrease in LEP amplitude was observed in response to loading with nefopam (F = 19.1; p < 0.001) and placebo (F = 5.73 and p < 0.001), with no significant difference between nefopam and placebo and no change in SEP characteristics. Conclusions: In this study, nefopam did not exhibit any effects on dyspnoea.